2023
DOI: 10.1002/joe.22192
|View full text |Cite
|
Sign up to set email alerts
|

How consumers in different cultural backgrounds prefer advertising in green ads through Hofstede's cultural lens? A cross‐cultural study

Abstract: When entering foreign markets, effective advertising appeals are usually employed in advertising to convey local consumers how the products and services will satisfy their wants or needs. The purpose of this cross‐cultural study is to investigate the consumers’ differences between a developed economy (USA) and an emerging economy (Thailand) based on Hofstede's cultural dimensions and the advertising appeal in green advertisements. This study investigates the role played by cultural and economic differences on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…The relationship between culture and behavior has received much attention [52]. Recent studies have shown that cultural values can affect different behaviors, including those of university students [53], tourists [54,55], and consumers [56,57]. These behaviors can vary among existing generations and emerging generations, which may have different traits due to intergenerational differences [58].…”
Section: Cultural Values and Pebmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between culture and behavior has received much attention [52]. Recent studies have shown that cultural values can affect different behaviors, including those of university students [53], tourists [54,55], and consumers [56,57]. These behaviors can vary among existing generations and emerging generations, which may have different traits due to intergenerational differences [58].…”
Section: Cultural Values and Pebmentioning
confidence: 99%
“…Personal long-term orientation was also found to be associated with PEBs [59]. A recent study conducted by Ruanguttamanun [57] investigated consumer differences between a developed economy (USA) and an emerging economy (Thailand) based on Hofstede's cultural dimensions and the advertising appeal of green advertisements, which play an important role in raising consumer concerns about environmental issues. The study revealed that the cultural value differences in Hofstede's dimensions are evident in the advertising appeal of green advertisements.…”
Section: Cultural Values and Pebmentioning
confidence: 99%
“…Therefore, although the cultures utilized in the present study are modern western cultures, some cross‐cultural scholars consider these non‐trivial cultural differences, making the two countries suitable for cross‐cultural comparison (Ford et al, 2018). Studying these two cultures helps bring novel insights into cross‐cultural studies, as comparisons between various western cultures are not common, compared to comparisons between U.S. and Asian cultures (Muk et al, 2014; Pacheco‐Baldo, 2021; Ruanguttamanun, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, on a macro level, such difference reflects the effectiveness of distinct emotions across nations. A recent study found that while consumers from different nations preferred the same appeals, negative emotion appeal (fear and sadness) was more effective for the developing nation Thailand (in contrast to the United States) due to its feminine and uncertainty avoidance cultural orientation (Ruanguttamanun, 2023). Therefore, we contend that distinct emotions can work very well for one culture or nation and may have a reverse effect on another.…”
Section: Limitations and Future Research Directionmentioning
confidence: 99%